Diagnostic Utility of a Novel Point-of-Care Test of Calprotectin for Periprosthetic Joint Infection After Total Knee Arthroplasty: A Prospective Cohort Study. (2nd June 2021) - Warren, Jared; Anis, Hiba K.; Bowers, Kathleen; Pannu, Tejbir; Villa, Jesus; Klika, Alison K.; Colon-Franco, Jessica; Piuzzi, Nicolas S.; Higuera, Carlos A.
Abstract : Background: Despite several synovial fluid biomarkers for the diagnosis of periprosthetic joint infection (PJI) having been investigated, point-of-care (POC) tests using these biomarkers are not widely available. Synovial calprotectin has recently been reported to effectively exclude the diagnosis of PJI. Thus, the objective of this study was to test the value of a calprotectin POC test for PJI diagnosis in patients undergoing total knee arthroplasty (TKA) using the 2013 Musculoskeletal Infection Society (MSIS) PJI diagnosis criteria as the gold standard. Methods: Synovial fluid samples were prospectively collected from 123 patients who underwent revision TKA at 2 institutions within the same health-care system from October 2018 to January 2020. The study was conducted under institutional review board approval. Data collection comprised demographic, clinical, and laboratory data in compliance with the MSIS criteria. Synovial fluid samples were analyzed by calprotectin POC tests in accordance with the manufacturer's instructions. Revisions were categorized as septic or aseptic using MSIS criteria by 2 independent reviewers blinded to the calprotectin results. Calprotectin test performance characteristics with sensitivities, specificities, positive predictive values, negative predictive values, and areas under the receiver operating characteristic curve (AUC) were calculated for 2 different PJI diagnosis scenarios: (1) a threshold of ≥50 mg/L, and (2) a threshold of ≥14 mg/L. Results: According to the MSIS criteria, 53 revision TKAs were septic and 70 revision TKAs were aseptic. In the ≥50-mg/mL threshold scenario, the calprotectin POC performance showed a sensitivity of 98.1%, a specificity of 95.7%, a positive predictive value of 94.5%, a negative predictive value of 98.5%, and an AUC of 0.969. In the ≥14-mg/mL threshold scenario, the sensitivity was 98.1%, the specificity was 87.1%, the positive predictive value was 85.2%, the negative predictive value was 98.4%, and the AUC was 0.926. Conclusions: The calprotectin POC test has excellent PJI diagnostic characteristics, including high sensitivity and specificity in patients undergoing revision TKA. This test could be effectively implemented as a rule-out test. However, further investigations with larger cohorts are necessary to validate these results. Level of Evidence: Diagnostic Level I . See Instructions for Authors for a complete description of levels of evidence.